MĂNĂSTIRILE RUPESTRE ȘI DEZVOLTAREA TURISMULUI RELIGIOS ÎN REPUBLICA MOLDOVA - Moşin, Octavian; Opriş, Dorin (CEP USM, 2022)
The conceptualization of the tourist phenomenon has been the concern of several researchers. Thus, in the specialized literature, there is a diversity of interpretations given to the concept of "tourism". Broadly speaking, tourism is the whole spectrum that arises from the idea and/or action that involves the movement of human beings to a place other than their residence with recreational possibilities. Tourism is also presented as a ubiquitous, complex and multidisciplinary phenomenon that includes economic, social, political, artistic, anthropological, environmental, historical, geographical, educational, psychological, communicative, etc. aspects.
RUPESTRAL MONASTERIES AND THE DEVELOPMENT OF RELIGIOUS TOURISM IN THE REPUBLIC OF MOLDOVA
Keywords: religious tourism; monastery; sustainable development; cultural tourism